2022
DOI: 10.55123/sehatmas.v1i4.929
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Berhubungan dengan Pemilihan Tempat Persalinan di Wilayah Kerja Puskesmas Tarus

Abstract: Puskesmas Tarus is the only puskesmas in Kupang Regency that has always contributed to maternal death cases since 2016-2018. The number of maternal deaths at the Tarus Health Center in 2016 was 2 cases, in 2017 1 case and in 2018 1 case. The direct cause of maternal death at the Tarus Health Center in 2020 was due to heavy bleeding and preeclampsia and childbirth was carried out at home. Therefore, the decision to choose a health facility as a place of delivery is very important to help prevent the occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is hoped that this high level of maternal knowledge can be a reference in maternal health attitudes and behavior in selecting birth attendants for the safety and health of the mother and her baby in the future. 21 Although the results of this study provide evidence of a relationship between knowledge and the choice of place of birth, in this study it was also found Sitti Al Aaliatin Hamsah, Juminten Saimin, Asnia Zainudin 57 that 16 respondents (28.1%) chose a birth place that was not a health facility even though they had good knowledge, this was due to the lack of family support. obtained by the mother, the mother's closest family wants the mother to give birth at home because they think that the birthing process can be monitored directly by the family rather than in a health facility.…”
Section: The Relationship Between Knowledge and Choice Of Place Of De...mentioning
confidence: 53%
See 1 more Smart Citation
“…It is hoped that this high level of maternal knowledge can be a reference in maternal health attitudes and behavior in selecting birth attendants for the safety and health of the mother and her baby in the future. 21 Although the results of this study provide evidence of a relationship between knowledge and the choice of place of birth, in this study it was also found Sitti Al Aaliatin Hamsah, Juminten Saimin, Asnia Zainudin 57 that 16 respondents (28.1%) chose a birth place that was not a health facility even though they had good knowledge, this was due to the lack of family support. obtained by the mother, the mother's closest family wants the mother to give birth at home because they think that the birthing process can be monitored directly by the family rather than in a health facility.…”
Section: The Relationship Between Knowledge and Choice Of Place Of De...mentioning
confidence: 53%
“…In this research, it was found that respondents with low family incomes preferred delivery places outside health facilities such as at home with the help of a birth attendant, in contrast to mothers who had high family incomes who chose to give birth in health facilities. 21 Income is a reason for women to prefer home as a place to give birth, because they argue that choosing to give birth at home costs less than giving birth in a health facility. They think that by giving birth at home they can save money on delivery costs and the birth money can be diverted to pay for the services of health workers.…”
Section: The Relationship Between Income and Choice Of Place Of Deliverymentioning
confidence: 99%